Introduction of innovations in joint arthroplasty: Recommendations from the ‘EFORT implant and patient safety initiative’ - Søren Overgaard; Thomas M Grupp; Rob GHH Nelissen; Luca Cristofolini; Anne Lübbeke; Marcus Jäger; Matthias Fink; Sabine Rusch; Hassan Achakri; Francesco Benazzo; Dario Bergadano; Georg N Duda; et al. (EFORT Open Reviews, 2023)
With the implementation of the new MDR 2017/745 by the European Parliament, more robust clinical and pre-clinical data will be required due to a more stringent approval process. The EFORT Implant and Patient Safety Initiative WG1 ‘Introduction of Innovation’, combined knowledge of orthopaedic surgeons, research institutes, orthopaedic device manufacturers, patient representatives and regulatory authorities to develop a comprehensive set of recommendations for the introduction of innovations in joint arthroplasty within the boundaries of MDR 2017/745. Recommendations have been developed to address key questions about pre-clinical and clinical requirements for the introduction of new implants and implant-related instrumentation with the participation of a steering group, invited by the EFORT Board in dialogue with representatives from European National Societies and Speciality Societies. Different degrees of novelty and innovation were described and agreed on in relation to when surgeons can start, using implants and implant-related instrumentation routinely. Before any clinical phase of a new implant, following the pre-market clinical investigation or the equivalent device PMCF pathway, it is a common understanding that all appropriate pre-clinical testing (regulatory mandatory and evident state of the art) – which has to be considered for a specific device – has been successfully completed. Once manufacturers receive the CE mark for a medical device, it can be used in patients routinely when a clinical investigation has been conducted to demonstrate the conformity of devices according to MDR Article 62 or full equivalence for the technical, biological and clinical characteristics has been demonstrated (MDR, Annex XIV, Part A, 3.) and a PMCF study has been initiated.